2009
DOI: 10.1371/journal.pone.0008349
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Pain and Inflammation in Juvenile and Adult Rats Fed a Ketogenic Diet

Abstract: The ketogenic diet is a high-fat, low-carbohydrate regimen that forces ketone-based rather than glucose-based cellular metabolism. Clinically, maintenance on a ketogenic diet has been proven effective in treating pediatric epilepsy and type II diabetes, and recent basic research provides evidence that ketogenic strategies offer promise in reducing brain injury. Cellular mechanisms hypothesized to be mobilized by ketone metabolism and underlying the success of ketogenic diet therapy, such as reduced reactive ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
132
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(140 citation statements)
references
References 50 publications
5
132
2
1
Order By: Relevance
“…Specifi cally, both chronic pain and epilepsy are characterized by enhanced neuronal excitability, and whatever the relevant mechanisms may be, metabolic approaches toward treatment (e.g., the KD, inhibition of glycolysis through fasting or 2-DG, etc.) can alleviate neuropathic pain ( 14,176 ). Additionally, ASDs are often prescribed for chronic pain, further suggesting similarities in the pathophysiology of these two disorders ( 177 ).…”
Section: Pain and Infl Ammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifi cally, both chronic pain and epilepsy are characterized by enhanced neuronal excitability, and whatever the relevant mechanisms may be, metabolic approaches toward treatment (e.g., the KD, inhibition of glycolysis through fasting or 2-DG, etc.) can alleviate neuropathic pain ( 14,176 ). Additionally, ASDs are often prescribed for chronic pain, further suggesting similarities in the pathophysiology of these two disorders ( 177 ).…”
Section: Pain and Infl Ammationmentioning
confidence: 99%
“…Additionally, ASDs are often prescribed for chronic pain, further suggesting similarities in the pathophysiology of these two disorders ( 177 ). In juvenile and adult rats, the KD reduced pain, as assessed by increased latency to hind-paw withdrawal in a test of thermal nociception, and infl ammation, as measured by hind-paw swelling in response to injection of the immune-potentiator, Freund's complete adjuvant ( 176 ). Despite attaining similar levels of circulating ketone bodies, the anti-infl ammatory and hypo-algesic effects of the KD were more prominent in juvenile mice ( 176 ).…”
Section: Pain and Infl Ammationmentioning
confidence: 99%
“…Furthermore, a greater relative improvement in insulin sensitivity has been observed in obese patients following a LC-HF diet than in those on a calorie-and fat-restricted diet with normal carbohydrate content (44). In patients with type 2 diabetes, low-carbohydrate diets have been shown to improve glycemic control (24,26,27,42) and are suggested to reduce the likelihood of exacerbating existing hyperinsulinemia (38). It has also been suggested that LC-HF diets could protect against the development of type 2 diabetes mellitus (1,29).…”
mentioning
confidence: 99%
“…These diets are used to treat epilepsy in children but are currently also under intense research as a potential treatment option for brain (48) and prostate cancer (23) and neurodegenerative diseases such as Alzheimer's and Parkinson's diseases (50). In addition, it has been suggested that ketogenic diets may offer a new therapeutic opportunity for controlling pain and peripheral inflammation (42). Animal studies allow investigation of diet effects in a more controlled and standardized environment than can be achieved in humans.…”
mentioning
confidence: 99%
“…As a nonpharmacologic therapy, the ketogenic diet also does not have any known interactions with antibiotics or anticonvulsants. Lastly, some evidence would suggest a possible anti-inflammatory action, which may explain its success specifically for status epilepticus caused by encephalitis (10).…”
Section: The Fat Is In the Fire: Ketogenic Diet For Refractory Statusmentioning
confidence: 99%